(untitled) (Research, Society and Development, 2021)
The purpose of this article is to report a clinical case of a patient with TMD, evaluating the efficacy of dry needling as a treatment. The study was carried out in a dental clinic of higher education, where the evaluation of the patient was performed in order to conclude a correct diagnosis complementing with the use of dry needling. Patient, female, 38 years old, reported pain throughout the muscular region of the face, where it was more pronounced in the parotid-massometric region, with spreading to the temporal region. After performing the evaluation in addition to the percussion and palpation tests, the patient was diagnosed with spreading myofascial pain, in addition to headache attributed to TMD bilaterally. As a therapeutic approach, the dry needling technique was performed, in addition to the orientation of Cognitive Behavioral Therapy, since the patient reported having parafunctional habits. The techniques used produced an effective improvement to the patient, where the patient reports a relief of the muscular pains when performing the dry needling.